2011
DOI: 10.3354/meps08983
|View full text |Cite
|
Sign up to set email alerts
|

Summer dynamics of Alexandrium ostenfeldii (Dinophyceae) and spirolide toxins in Cork Harbour, Ireland

Abstract: Proliferations of toxic Alexandrium spp. have adversely affected the shellfish aquaculture industry worldwide. A. ostenfeldii can produce several biotoxins, including the recently characterised fast-acting toxins spirolides (SPX). A dual labelling fluorescent in situ hybridisation (FISH) assay was developed for discriminating simultaneously between the closely related taxa A. ostenfeldii and A. peruvianum. Surveys were undertaken throughout the summers of 2006, 2007 and 2008 in Cork Harbour, Ireland, where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Balech (1995) similarly reported a mix of straight and curved margins in material from North America; however, he considered this an exception. The s.a. plate, which has commonly been considered the most important feature for the delineation of A. peruvianum from A. ostenfeldii (Balech 1995, Touzet et al 2011, was also found to be problematic. Most of the A. peruvianum isolates contained significant amounts (20%-30%) of the doorlatch shaped s.a. plates typical for A. ostenfeldii.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Balech (1995) similarly reported a mix of straight and curved margins in material from North America; however, he considered this an exception. The s.a. plate, which has commonly been considered the most important feature for the delineation of A. peruvianum from A. ostenfeldii (Balech 1995, Touzet et al 2011, was also found to be problematic. Most of the A. peruvianum isolates contained significant amounts (20%-30%) of the doorlatch shaped s.a. plates typical for A. ostenfeldii.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent assignment has furthermore been complicated by the lack of consensus regarding the weight of the different diagnostic features: while some investigators have given priority to the s.a. shape , others considered the anterior 1′ margin most important (MacKenzie et al 1996, Kremp et al 2009). In addition to these inconsistencies, morphogenetic identification is not simple either, despite the availability of extensive sequence data and recognition of specific genetic signatures (Touzet et al 2011). GenBank contains numerous identical sequences from isolates assigned to A. ostenfeldii and A. peruvianum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However although it is known to occur in Cork Harbour, it appears to exist in much lower numbers then either A. minutum or A. tamarense (WE) (Touzet et al, 2011). A.…”
Section: Discussionmentioning
confidence: 95%
“…Probes are available for detecting toxic species of the marine pennate diatom genus Pseudo-nitzschia that are associated with domoic acid in natural samples (e.g., Scholin et al, 1996Scholin et al, & 1997 as well as for toxic species in the important bloom forming microalgae, Chrysochromulina (Simon et al, 2000) and Prymnesium (Simon et al, 2000;Töbe et al, 2006) from marine and brackish environments. Probes targeting the different species of the toxigenic paralytic shellfish toxin (PSP) producing dinoflagellate genus Alexandrium include those detecting the North American Alexandrium tamarense ribotype (Miller and Scholin 1998;John et al, 2003), the toxic Temperate Asian ribotype (Hosoi-Tanabe and Sako 2005), the non-toxic Western European ribotype (John et al, 2005, Touzet et al 2008, the non-toxic Mediterranean species complex (John et al, 2005), A. minutum, the non-toxic co-occurring morphologically similar species A. andersoni in Irish coastal waters (Touzet and Raine 2007;Touzet et al 2008) and A. peruvianum (Touzet et al, 2011) and the spirolide producing taxa A. ostenfeldii (John et al, 2003, Touzet et al, 2011 All of these probes have been applied in field studies (John et al, 2005;Anderson et al, 2005). A set of FISH probes are also developed (John et al, in prep.…”
Section: Wwwintechopencommentioning
confidence: 99%